2021
DOI: 10.1155/2021/7199888
|View full text |Cite
|
Sign up to set email alerts
|

An Adaptive Operational Modal Analysis Method Using Encoder LSTM with Random Decrement Technique

Abstract: A new parameter identification method under non-white noise excitation using transformer encoder and long short-term memory networks (LSTMs) is proposed in the paper. In this work, the random decrement technique (RDT) processing of the data is equivalent to eliminating the noise of the raw data. In general, the addition of the gate in LSTM allows the network to selectively store data, which avoids gradient disappearance and gradient explosion to a certain extent. It is worthwhile mentioning that the encoder ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…The experimental results showed that the proposed algorithm has higher recommendation accuracy than other algorithms such as CF. Reference [10] proposed a recommendation model based on gated recurrent unit (GRU) and the relationship between courses. Combined with the relationship between courses, GRU and Softmax function were used to recommend courses.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results showed that the proposed algorithm has higher recommendation accuracy than other algorithms such as CF. Reference [10] proposed a recommendation model based on gated recurrent unit (GRU) and the relationship between courses. Combined with the relationship between courses, GRU and Softmax function were used to recommend courses.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, many researchers have tried to obtain modal parameters directly by neural networks. Qin et al (Qin et al, 2021) proposed a new parameter identification method under non-white noise excitation using the transformer encoder and long short-term memory networks (LSTMs) and applied the random decrement technique (RDT) to preprocess the noised input data. Fang et al (Fang et al, 2017) developed an unsupervised-learning CNN to identify the modal parameters only from acceleration signals.…”
Section: Introductionmentioning
confidence: 99%